Factors Influencing Organizational Commitment, Job Involvement, and Work-Life Balance Among Employees of Banks : An Analysis - Chandel, Siddharth; Chanda, Kiran; Chandel, Kulbhushan (Prabandhan: Indian Journal of Management, 2023)
Organizational commitment is the degree to which employees trust, admit, and wish to continue with the organization. Some investigators have well-thought-out that organizational rules and guidelines are the foundation of work-life conflicts. It has also been recognized that the role of corporate culture is very significant in maintaining the work-life balance among employees in an organization. Purpose : The review of the literature revealed that no authoritative and comprehensive study had so far been focused on organizational commitment, job involvement, and work-life balance among employees of banks under study, and there existed a research gap among various studies undertaken so far. The present research work would help bridge the gaps among the various studies undertaken. Methodology : The present research work is exploratory and descriptive. Both secondary and primary data were collected to accomplish the objectives undertaken for the present research work. Findings : The analysis and interpretation based upon the methodology used led to the conclusion that the factors influencing organizational commitment and job involvement might significantly contribute towards work-life balance. Practical Implications : The study was carried out on banking institutions. Therefore, suitable strategies should be framed for enhancing organizational commitment and job involvement and maintaining work-life balance among employees in the banking sector.